High Diversity of Tick-associated Microbiota from Five Tick Species in Yunnan, China - Jie Zhang; Xue-Bing Ni; Zi-Yun Chen; Yun Zhang; Ran Wei; Zheng-Da Gong; Dai-Yun Zhu; Xiao-Ming Cui; Zong-Ti Shao; Hong-Bo Liu; Yu-Qiong Li; Jian Wang; et al. (Zoonoses, 2023)
Ticks are obligate blood-sucking vectors for multiple zoonotic diseases. In this study, tick samples were collected from Yunnan Province, China, which is well-known as the “Global Biodiversity Hotspot” in the world. This study aimed to clarify the microbial populations, including pathogens, associated with ticks and to identify the diversity of tick-borne microbiota in this region. The 16S rRNA full-length sequencing from pooled tick DNA samples and PCR amplification of pathogenic genera from individual samples were performed to understand tick-associated microbiota in this region. A total of 191 adult ticks of 5 tick species were included and revealed 11 phyla and 126 genera bacteria, including pathogenic Anaplasma , Ehrlichia , Candidatus Neoehrlichia, Rickettsia , Borrelia , and Babesia . Further identification suggested that Rickettsia sp. YN01 was a variant strain of Rickettsia spp. IG-1, but Rickettsia sp. YN02 and Rickettsia sp. YN03, were potentially two new SFGR species. This study revealed the complexity of ecological interactions between host and microbe and provided insight for the biological control of ticks. A high microbial diversity in ticks from Yunnan was identified, and more investigation should be undertaken to elucidate the pathogenicity in the area.